PENGARUH INVESTMENT OPPORTUNITY SET DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DIMEDIASI OLEH HARGA SAHAM SEKTOR PERKEBUNAN - Ragil Saputra, Adi Hasan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
The purpose of this study is to examine the effect of investment opportunity set (IOS), profitability on firm value is intervening by stock prices. This study used 14 plantation sector companies listed on the Indonesia Stock Exchange during 2013-2017 with a sampling technique that was purposive sampling using structural equation modeling (SEM) analysis. The results showed that IOS had no affect stock prices. Profitability has a positive effect on stock prices. IOS has a positive effect on company value. Profitability had no effect the value of the company. Stock prices have a positive effect on firm value. IOS had no effect the value of the company intervening by stock prices. Profitability has a positive effect on firm value intervening by stock prices. The advice given is for company management and the government to carry out domestic and international synergies. Domestic synergy aims to create product downstream, political, legal and economic stability. While international synergy aims to secure the export portion, sustainable plantation socialization and open new markets